2015
DOI: 10.1002/2015gl063289
|View full text |Cite
|
Sign up to set email alerts
|

Substorm current wedge composition by wedgelets

Abstract: Understanding how a substorm current wedge (SCW) is formed is crucial to comprehending the substorm phenomenon. One SCW formation scenario suggests that the substorm time magnetosphere is coupled to the ionosphere via “wedgelets,” small building blocks of an SCW. Wedgelets are field‐aligned currents (FACs) carried by elemental flux transport units known as dipolarizing flux bundles (DFBs). A DFB is a magnetotail flux tube with magnetic field stronger than that of the ambient plasma. Its leading edge, known as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 41 publications
5
85
1
Order By: Relevance
“…That figure shows region 2 sense FACs forming at the leading edge and a dominant region 1 sense current associated with the main part of the bubble, with longitudinal velocity on the earthward side and a region of earthward velocity on the tailward side. This FAC morphology is also consistent with observations of FACs at dipolarization fronts [ Yao et al , ; Sun et al , ; Liu et al , ] which are believed to represent the leading edge of flow bursts. A quantitative evaluation of the motion of the streamer FACs compared to the local ionospheric convection can be used to further examine mechanisms for FAC generation as suggested by numerical simulations and magnetotail observations of dipolarization fronts.…”
Section: Discussionsupporting
confidence: 90%
“…That figure shows region 2 sense FACs forming at the leading edge and a dominant region 1 sense current associated with the main part of the bubble, with longitudinal velocity on the earthward side and a region of earthward velocity on the tailward side. This FAC morphology is also consistent with observations of FACs at dipolarization fronts [ Yao et al , ; Sun et al , ; Liu et al , ] which are believed to represent the leading edge of flow bursts. A quantitative evaluation of the motion of the streamer FACs compared to the local ionospheric convection can be used to further examine mechanisms for FAC generation as suggested by numerical simulations and magnetotail observations of dipolarization fronts.…”
Section: Discussionsupporting
confidence: 90%
“…The additional ground magnetic field perturbation may come about through small-scale up-down current pairs within MLT sectors that are not resolved by AMPERE. It has been proposed that the substorm current wedge could arise from the summation of a series of elemental currents (Birn & Hesse, 2013;Liu et al, 2015;Lyons et al, 2012Lyons et al, , 2013Rostoker, 1991;Zhang et al, 2011), which may or may not be linked to magnetospheric flows. Forsyth et al (2014) showed that a large-scale substorm current wedge covering 4 hr of MLT had a longitudinal structure consisting of more than thirty~100 km wide north-south aligned current sheets.…”
Section: Time Profiles Of Postonset Facsmentioning
confidence: 99%
“…These current layers have thicknesses estimated to be comparable to plasma sheet proton gyroradius (~500 to ~1,000 km; e.g., Liu et al, ; Runov et al, ; Sun, Fu, Pu, et al, ). They are also associated with kinetic features (e.g., H. S. Fu et al, ; Sergeev et al, ; Sun, Fu, Pu, et al, ) and field‐aligned currents (e.g., Liu et al, , ; Sun et al, , Sun, Fu, Parks, et al, ) as well.…”
Section: Introductionmentioning
confidence: 99%